Glutathione S-transferase and gamma-glutamyl transpeptidase activities in cultured rat hepatocytes treated with tocotrienol and tocopherol - Ong, F.B.; Wan Ngah, W.Z.; Shamaan, N.A.; Md. Top, A.G.; Marzuki, A.; Khalid, A.K. (1993)
1. The effect of tocotrienol and tocopherol on glutathione S-transferase (GST) and gammaglutamyl transpeptidase (GGT) activities in cultured rat hepatocytes were investigated. 2. Tocotrienol and tocopherol significantly decreased GGT activities at 5 days in culture but tocotrienol also significantly decreased GGT activities at 1-2 days. 3. Tocotrienol and tocopherol treatment significantly decreased GST activities at 3 days compared to the control but tocotrienol also decreased GST activities at 1-3 days. 4. Tocotrienol showed a more pronounced effect at a dosage of greater than 50 μM tocotrienol at 1-3 days in culture compared to the control. © 1993.